The Influence of CEO Characteristics on Corporate Sustainability Growth: The Moderating Role of the Audit Committee in Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange - Khairunisa Leginaputri; Dina Patrisia (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to identify the influence of Chief Executive Officer characteristics (Gender, Experience, Ownership) on Corporate Sustainability Growth (CSG) with Audit Committee Expertise as the moderation variable. This study uses panel data consisting of 26 companies listed in the food and beverage sector on the Indonesia Stock Exchange with an observation period of 2019 to 2023, resulting in a total sample of 130 observations. The data analysis tool in this study is Moderated Regression Analysis (MRA). The results showed that CEO Ownership and CEO Experience had a significant positive influence on CSG, while CEO Gender did not show a significant influence. In addition, the Audit Committee Expertise plays the role of a moderation variable in the relationship between CEO Experience and CSG, as well as between CEO Ownership and CSG. This research contributes to the literature by emphasizing the important role of both CEO and Audit Committee Expertise characteristics in improving company sustainability, as well as providing insights for readers and decision-makers in ensuring that the company's sustainability strategy is in line with the organization's long-term goals.